A population based case-control study of cataract and inhaled corticosteroids. Issue 10 (23rd September 2003) - Smeeth, L; Boulis, M; Hubbard, R; Fletcher, A E
Abstract : Background/aims: Exposure to systemic corticosteroid use is known to be associated with a risk of cataract. Whether low doses of inhaled corticosteroids are associated with an increased risk of cataract is not known. This study was undertaken to quantify the risk of cataract associated with the use of inhaled corticosteroids and assess whether there is a dose-response relation. Methods: A population based case-control study based on the General Practice Research Database in the United Kingdom. 15 479 people with cataract and 15 479 controls were matched for age, sex, practice, and observation period. Results: The crude odds ratio for the association between any recorded exposure to inhaled corticosteroids and cataract was 1.58 (95% CI 1.46 to 1.71), reduced to 1.10 (95% CI 1.00 to 1.20) after adjustment for systemic corticosteroid exposure and consultation rate. There was a dose-response relation, the adjusted odds ratio rising from 0.99 (95% CI 0.87 to 1.13) at daily doses up to 400 μg to 1.69 (95% CI 1.17 to 2.43) for daily doses greater than 1600 μg. The association was also stronger with increasing duration of use. Conclusion: Higher doses and longer duration of exposure to inhaled corticosteroids are associated with an increased risk of cataract. The lowest doses compatible with good control of airways disease should be used. The risk of cataract associated with high doses of inhaled corticosteroids needs to be more widely appreciated.